A matched comparison of human papillomavirus–induced squamous cancer of unknown primary with early oropharynx cancer. (31st October 2017) - Ross, Richard Blake; Koyfman, Shlomo A.; Reddy, Chandana A.; Houston, Narcissa; Geiger, Jessica L.; Woody, Neil M.; Joshi, Nikhil P.; Greskovich, John F.; Burkey, Brian B.; Scharpf, Joseph; Lamarre, Eric D.; Prendes, Brandon; et al.
Abstract : Objectives/Hypothesis: Patients with human papillomavirus (HPV)–induced cancer of unknown primary (CUP) are generally excluded from clinical trials, despite surgical series reporting detection rates of occult oropharynx primaries of >80%. We performed a matched‐pair analysis to compare outcomes between T0N1‐3M0 HPV+ CUP and T1‐2N1‐3M0 HPV+ oropharynx known primary (OPX). Study Design: Retrospective cohort study at a single institution. Methods: Patients with early T stage, node positive HPV+ OPX or CUP treated with curative intent between 1998 and 2016 were identified. For a subgroup of CUP patients with an unknown HPV status, we imputed HPV status and included patients with a >80% probability of being HPV+. Cohorts were matched based on patient demographics using a nearest neighbor propensity technique. After matching, patients were grouped according to either a favorable or unfavorable risk stratification designations per current NRG Oncology clinical trial enrollment criteria. Disease‐free survival (DFS) and overall survival (OS) were calculated using Kaplan‐Meier analysis. Results: Of 298 patients with T1‐2N1‐3 OPX, 48 were matched to 48 HPV+ CUP patients (32 with confirmed and 16 imputed HPV status). Median follow‐up for CUP (34.1 months) and OPX (27.8 months) patients were similar ( P = .23).There were no significant differences between the CUP and OPX groups for 3‐year DFS (89% vs. 85%, P = .44), and 3‐year OS (91% vs. 91%, P = .11), respectively. Conclusions: Patients with T0N+M0 HPV‐induced CUP have similar survival outcomes to matched patients with T1‐2N+M0 HPV+ OPX. These patients can reasonably be included in clinical trials investigating the role of treatment deintensification and risk stratified similar to patients with early‐stage known primary OPX cancer. Level of Evidence: 4. Laryngoscope, 128:1379–1385, 2018